Pengujian Blackbox pada Website Sistem Pemesanan Travel Online Gemilang Travel Berbasis Teknik Equivalence Partitions - Apriliandra, Alif Rizqi; Nuryasin, Ilyas (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Online travel websites, such as Gemilang Travel, face complexities and dynamics that can result in potential errors and system failures. This can result in a bad experience for users and losses for the company. This research aims to identify potential errors that may occur in Gemilang Travel's Online Travel Booking System through Blackbox testing with the Equivalence Partitions technique. Blackbox testing is done without knowing the internal details of the system, so the focus is on the behavior of the system from the user's point of view. The Equivalence Partitions technique helps divide data input values into equivalent partitions based on expected system behavior. In this context, researchers used Blackbox testing with the Equivalence Partitions technique to identify potential errors. The testing methodology involved creating test cases, dividing Equivalence Partitions for each data input category, implementing the tests, and analyzing the test results. The test results show that based on 16 test scenarios that have fulfilled the designed scenarios and based on the calculation of equation 1 shows an EP test success percentage of 100%. This ticket booking application operates well and runs according to its function.